Inclusiveness of Urban Land Administration in the City of Lusaka, Zambia - Lupale, Mubanga; Hampwaye, Godfrey (Bulletin of Geography. Socio-economic Series, 2019)
Many cities in developing countries are experiencing urbanization characterised by the continu-ous proliferation of informal settlements. In the City of Lusaka over 70 percent of residents live in informal settlements. The purpose of this paper is to provide an account of how inclusive land administration is in the City of Lusaka using the perspective of good governance principles. The sample comprised 10 key informants purposively selected from government institutions/ civil society organisations and 60 respondents conveniently drawn from informal settlements. The findings were analysed thematically and using descriptive statistics. The findings show that there is need to create policies and legislation that assists in developing viable, liveable and inclusive townships. Most indicators of the five good governance principles recorded negative responses of at least 60 per cent. Formal urban land development arrangements in the city have not been able to cope with the demands of the majority of urban residents. The study suggests that land and housing policies be revised to serve a broader purpose beyond the provision of shelter in order to suit the dynamic and contemporary needs of specific societies. Further re-search is needed on tenure responsive land use planning in order to understand existing commu-nity dynamics (economic and social support networks) and implement practical changes for tackling informality if Zambian cities and communities are to be sustainable and resilient.